Être correspondant régional en Tunisie : De l’aliénation au pouvoir à la liberté totale - Hamida El Bour (L’Année du Maghreb)
The uprisings that took place in Tunisia from 17th of December 2010 to 14 January 2011 show how the mainstream Tunisian media made a blackout on what was happening in the regions inside the country. This is how did the media system during the former Ben Ali’s regime era used to deal with the real concerns of the citizens. The coverage of the local events was far from the rules of the proximity journalism which is based on journalistic practice that reflect the reality of the people and their daily life problems. This paper compare between the Tunisian media coverage of the local news before and after the revolution through the experience of 16 local correspondents out of 27 working for the Tunis Afrique Presse news agency, a public media the only news house to get a correspondents network in all the regions of Tunisia since the sixties of the last century. We conducted a qualitative survey among these correspondents asking about the local news agenda and the correspondents’ choice of priorities to cover the news before and after January 2011. What changed in their practice, their behavior and their discourse? They said that censorship and self-censorship were overwhelming the way of covering the news in the regions and that the main role for the reporter is very limited. They were told what to cover and how. The local news agenda was linked to the politics and the local authorities activities. No criticism was admitted. The correspondents mentioned two essential fields for «safe media coverage» : Tourism and culture. Today, within the context of press freedom the correspondent feel themselves as the voice of voiceless people. The power of the media is challenging the political power which can no longer use the media for propaganda purposes by intervening in the correspondents work.